2020
DOI: 10.1186/s13018-020-01826-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of facet-joint degeneration on the in vivo motion of the lower lumbar spine

Abstract: Objective: This research studied the in vivo motion characteristics of the L3-S1 lumbar spine with facet-joint degeneration during functional activities. Methods: Thirteen male and 21 female patients with facet-joint degeneration at the L3-S1 spinal region were included in the study. The L3-S1 lumbar segments of all the patients were divided into 3 groups according to the degree of facet-joints degeneration (mild, moderate, or severe). The ranges of motion (ROM) of the vertebrae were analyzed using a combinati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…While playing an important role in the physiological function of the lumbar spine, facet joints also carry 6%–30% of the axial compressive load ( Yin et al, 2020 ). This loading may also accelerate the degeneration of the facet joint, especially in people over 60 years of age ( Yin et al, 2020 ). Such degeneration usually begins with changes in the articular cartilage and eventually leads to destruction of the entire joint and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While playing an important role in the physiological function of the lumbar spine, facet joints also carry 6%–30% of the axial compressive load ( Yin et al, 2020 ). This loading may also accelerate the degeneration of the facet joint, especially in people over 60 years of age ( Yin et al, 2020 ). Such degeneration usually begins with changes in the articular cartilage and eventually leads to destruction of the entire joint and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While playing an important role in the physiological function of the lumbar spine, facet joints also carry 6%-30% of the axial compressive load (Yin et al, 2020). This loading may also accelerate the degeneration of the facet joint, especially in people over 60 years of age (Yin et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…However, if osteoarthritis occurs, the joint load of abnormal joint force can be as high as 47% [ 21 ], which also increases the risk of low back pain. Yin et al [ 16 ] found that with the increase in facet degeneration, the initial increase in lumbar range of motion decreased, which would change the stability of the lumbar spine. Therefore, it is very important to delay facet degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of LFJs, Li and his colleagues [ 15 ] were the first to use this technique to quantify the in vivo kinematics of lumbar facets in nonfunctional weight-bearing positions. Yin [ 16 ] also studied the effect of degenerative facets on the range of motion of the lumbar spine through this system. Although these studies have greatly analyzed the kinematics of LFJs in vivo under functional loading, their research direction is limited to either non-weight bearing or flexion and extension.…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of people detoriation of the facet joints. 6 The probability of wear and tear of disc usually increase with age and may not give rise to any symptoms, but with progression it can cause severe LBP. 7 A comprehensive clinical history and physical examination can usually diagnose severity of illness that may be resulting in back pain.…”
Section: Introductionmentioning
confidence: 99%